REACTUALIZATION OF THE ISLAMIC EDUCATION SYSTEM IN RESPONDING TO THE CHALLENGES OF THE WORLD OF EDUCATION - Yahya; Winsidi (IAI AGUS SALIM METRO LAMPUNG, 2022)
Islamic education is a system that involves all components of education that are interrelated in an integrated manner to achieve the goals of Islamic education. As a system, Islamic education consists of components that are functionally interrelated. If there is good cooperation between the components, the system will run or work optimally. For this reason, the preparation of planning and development of Islamic education needs to use a systems approach. The Islamic education system must be based on three main foundations, namely: a religious basis, a philosophical basis, and a scientific basis. The third base should be the main basis for the formulation of various components of education, including the formulation and development of the curriculum, as well as the management of institutions and the future of Islamic education.